SISTEM KARIR DAN MODEL PENGEMBANGANNYA DI ORGANISASI TANPA BATAS (Boundary-Less Organization) - Kurniawati P, Endah (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2005)
In global era, organization or company has to develop, from traditional model to be opened system. In opened organizational system, level of career is not vertical but horizontal, and not linear but spiral. In this case, the steering of career is not the company, but individual. Each person is always claimed to develop his or his knowledge and skill according to the requirement. What significant is not the number of title, much training or courses, but evidence of achievement and job experience.Keywords: infinite organizational and development of [his/its] career